187k views
5 votes
Dy/dx if y = Ln (2x3 + 3x).

1 Answer

3 votes

Answer:


(6x^2+3)/(2x^3+3x)

Explanation:

You need to apply the chain rule here.

There are few other requirements:

You will need to know how to differentiate
\ln(u).

You will need to know how to differentiate polynomials as well.

So here are some rules we will be applying:

Assume
u=u(x) \text{ and } v=v(x)


(d)/(dx)\ln(u)=(1)/(u) \cdot (du)/(dx)


\text{ power rule } (d)/(dx)x^n=nx^(n-1)


\text{ constant multiply rule } (d)/(dx)c\cdot u=c \cdot (du)/(dx)


\text{ sum/difference rule } (d)/(dx)(u \pm v)=(du)/(dx) \pm (dv)/(dx)

Those appear to be really all we need.

Let's do it:


(d)/(dx)\ln(2x^3+3x)=(1)/(2x^3+3x) \cdot (d)/(dx)(2x^3+3x)


(d)/(dx)(\ln(2x^3+3x)=(1)/(2x^3+3x) \cdot ((d)/(dx)(2x^3)+(d)/(dx)(3x))


(d)/(dx)(\ln(2x^3+3x)=(1)/(2x^3+3x) \cdot (2 \cdot (dx^3)/(dx)+3 \cdot (dx)/(dx))


(d)/(dx)(\ln(2x^3+3x)=(1)/(2x^3+3x) \cdot (2 \cdot 3x^2+3(1))


(d)/(dx)(\ln(2x^3+3x)=(1)/(2x^3+3x) \cdot (6x^2+3)


(d)/(dx)(\ln(2x^3+3x)=(6x^2+3)/(2x^3+3x)

I tried to be very clear of how I used the rules I mentioned but all you have to do for derivative of natural log is derivative of inside over the inside.

Your answer is
(dy)/(dx)=((2x^3+3x)')/(2x^3+3x)=(6x^2+3)/(2x^3+3x).

User David Arenburg
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.